Digital Storytelling Guideline Applied with Inclusive Design for Museum Presentation from Experts and Audiences Perspectives for Youth - Kittichai Kasemsarn; David Harrison; Farnaz Nickpour (My University, 2023)
The majority of young tourists are not interested in museums since most presentations do not make a connection with this group.Moreover, most digital storytelling presentation guidelines are created based on expert recommendations, and not on audience perspectives and needs.Hence, the aim of this research is to cocreate and propose a digital storytelling presentation guideline including both experts' and audiences' views to motivate young tourists to engage in museums.For experts' recommendations, seventeen face-to-face interviews were conducted.For audiences' views, thirty-seven interviews were set up to understand what they really need.As a result, this study creates nine factors for digital storytelling presentation guidelines for museums.The value of this guideline is to propose: (1) on-site presentations at the museums; (2) virtual online presentations; and (3) short presentations to attract prospective tourists to come to museums.
Keywords: Guideline; Presentation (obstetrics); Digital Storytelling; Digital Storytelling and Education